Common agricultural policy support to silvopasture in the European Atlantic region - Santiago-Freijanes, Jose Javier; Rodríguez-Rigueiro, Francisco Javier; Ferreiro-Domínguez, Nuria; López-Díaz, Ma Lourdes; Rigueiro-Rodríguez, Antonio; Castro, Marina; González-Hernández, María Pilar; Fernández-Lorenzo, Juan Luis; Romero-Franco, Rosa; García-Berrios, Julian Jesús; Hallez, Tobi; Anzilotti, Solaria; et al. (Frontiers in Forests and Global Change, 2025)
Agroforestry practices are sustainable forms of land management recognized by the Food and Agriculture Organization (FAO) and the European Commission (EC). These organizations have established mechanisms to promote agroforestry globally. However, the policies they create often lack monitoring and thorough impact evaluation. To effectively analyze how policies promote agroforestry, it is crucial to consider the scale and context in which these practices are implemented. Policies should be tailored to specific socioeconomic and environmental contexts to ensure their relevance and effectiveness. The best practices that emerge can be applied to similar situations. The objective of this study was to analyze the current state of silvopasture in the Atlantic region of Europe and the Common Agricultural Policy (CAP) measures associated with the Rural Development Programs (RDPs). The goals are to enhance our understanding of how sustainable land use systems are promoted and to provide insights that can foster agroforestry across Europe. The Atlantic region is characterized by a significant intensification of agricultural activities, with a very low proportion of silvopasture, mostly in the Northern Atlantic regions. Agroforestry is recognized for its ability to provide ecosystem services that sequester carbon and enhance biodiversity and productivity in the Central Atlantic Region of Europe by promoting hedgerows or reducing forest fires in the Southern Atlantic regions. The CAP promotes agroforestry in some of these areas, primarily through agri-environmental measures. Political measures should prioritize the management, conservation, and implementation of silvopasture to increase sustainability across the European Union (EU). Efforts to promote silvopasture should be encouraged through both agroforestry eco-schemes and CAP Pillar II interventions.